Ungkapan Hal Yastawī, Mā Yastawī, dan Lā Yastawī dalam Al-Qur’an dan Perbandingan Maknanya - Bunga Indah; Abdul Halim (Aksioreligia, 2026)
This study aims to analyze the use of the expressions hal yastawī, lā yastawī, and mā yastawī in the Qur'an and to compare the meanings and rhetorical functions contained in each construction. The research employs a qualitative approach with a literature review method, analyzing Qur'anic verses containing these three expressions and examining various exegesis (tafsir) books and Arabic linguistic literature. The results indicate that the hal yastawī expression is dominated by the istifhām li al-nafyi function, which aims to reject the existence of value equivalence through rhetorical questions, there by producing a strong persuasive effect. Meanwhile, lā yastawī functions as nafyu al-mutlaq, which is firm, universal, and normative in negating the value equivalence between two compared objects. Furthermore, mā yastawī tends to be used as a form of empirical negation or nafyu al-hāl to state differences in value that can be observed realistically and rationally through various parables and phenomena that human senses can capture. All three expressions similarly demonstrate a rejection of the nature of value of the compared objects, yet they possess different semantic and balāghī (rhetorical) characteristics depending on the context of the verse. These findings indicate that the varied use of the expression yastawī in the Qur'an is part of the beauty of the Qur'anic uslūb (style) in conveying creedal, moral, and spiritual messages effectively.